2007
DOI: 10.1038/sj.bjc.6604032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic changes in the common 1p36 deletion in neuroblastoma tumours

Abstract: Chromosome 1p is frequently deleted in neuroblastoma (NB) tumours. The commonly deleted region has been narrowed down by loss of heterozygosity studies undertaken by different groups. Based on earlier mapping data, we have focused on a region on 1p36 (chr1: 7 765 595 -11 019 814) and performed an analysis of 30 genes by exploring features such as epigenetic regulation, that is DNA methylation and histone deacetylation, mutations at the DNA level and mRNA expression. Treatment of NB cell lines with the histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 39 publications
4
63
0
Order By: Relevance
“…2 Evidence indicates that the region between D1S508 and D1S244 markers on chr1p36 is one of the commonly deleted regions in NB. 3 There are 30 genes in this region and expression analysis of 4 of the 30 genes showed that two of them (CASZ1 and PIK3CD) are expressed at significantly lower levels in unfavorable NB as compared with favorable ones. 3 However, the tumor-suppressor functions of CASZ1 and PIK3CD have not been investigated.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…2 Evidence indicates that the region between D1S508 and D1S244 markers on chr1p36 is one of the commonly deleted regions in NB. 3 There are 30 genes in this region and expression analysis of 4 of the 30 genes showed that two of them (CASZ1 and PIK3CD) are expressed at significantly lower levels in unfavorable NB as compared with favorable ones. 3 However, the tumor-suppressor functions of CASZ1 and PIK3CD have not been investigated.…”
mentioning
confidence: 99%
“…3 There are 30 genes in this region and expression analysis of 4 of the 30 genes showed that two of them (CASZ1 and PIK3CD) are expressed at significantly lower levels in unfavorable NB as compared with favorable ones. 3 However, the tumor-suppressor functions of CASZ1 and PIK3CD have not been investigated. 3 CASZ1 maps to Chr1p36.22 and is a recently described zinc-finger (ZnF) transcription factor whose expression is upregulated during induction of NB and myoblast cell differentiation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In acute myeloid leukemia p110d is essential for PI3K activation and cell proliferation (Sujobert et al, 2005). The gene encoding p110d (PIK3CD) is also expressed in neuroblastoma , where it is occasionally mutated (Caren et al, 2007), and in breast cancer cells, where it stimulates chemotaxis in response to the epidermal growth factor (Sawyer et al, 2003). In contrast to the a-and b-isoforms of p110, the oncogenic activity of p110d is resistant to inhibitors of the MAP kinase pathway and does not require binding to RAS (Denley et al, 2008).…”
Section: Introductionmentioning
confidence: 99%